Performance of Candidate Varieties of Basmati Rice in Uniform Yield Trials (Plant Bulletin, 2024)
The primary focus of rice breeding research is now on developing high-yielding rice varieties with early maturing and physio-chemical features, such as improved cooking quality, aroma, and extra-long grain. This shift in focus is driven by the growing global demand for high-quality rice. Using traditional breeding methods to trait pyramid these extremely important traits while maintaining yield and quality is a challenging task. Good grain quality(aromatic), fertilizer responsiveness, and high-yielding varieties can help the farmers in Pakistan to increase their revenue despite global population growth and changing international market patterns. At the Rice Research Institute, Kala Shah Kaku (RRI KSK), new, improved, high-yielding, extra-long grain lines with the qualities of early maturity, small stature, and good cooking with aroma are being developed through traditional breeding methods. The present study aimed to assess the genetic variability of these lines in terms of paddy yield and to discover superior high-yielding cultivars suitable for widespread cultivation. There were notable variations in paddy yield among the different entries in the pooled analysis. The highest average paddy yield (5010 Kg/ha) was seen in entry 10640-10-1-1-1, followed by entry 10684-3-1-2 (4990 Kg/ha) and PK 10434-6-2-1 (4550 Kg/ha) and suggested for general cultivation based on their mean paddy yield. A strong positive correlation was seen between the grain thickness grading of over 2.2 mm and the number of panicles per plant. The overall quality of the Uniform Yield Trials of Fine rice samples can be reported as excellent for PK 10306-15-5, PK PB-8 and PK 10678-2-1-1 over check Basmati-515. There will be a simultaneous increase in grain yield with improvements in these qualities.
Keywords: traditional breeding , fertilizer responsiveness, rait pyramid, pooled analysis, aroma